Study on the heat transfer characteristics of mine roadway surrounding rock under periodic airflow temperature: Numerical simulation and experimental validation - Mingyan Guo; Yueping Qin; Dongyang Han; Fei Tang; Shibin Wang; Hairong Wang (Case Studies in Thermal Engineering)
Studying the effect of periodic airflow temperature on the heat dissipation of surrounding rock is the basis for revealing the causes of seasonal mine heat damage. In this work, a heat transfer mathematical model of roadway surrounding rock under periodic airflow temperature was established. By variable separation method, the model was divided into two parts: annual average component and periodic fluctuation component. Then we discretized the model and designed a solution program independently. Finally, a similar heat transfer experiment platform for roadway surrounding rock was set up and the simulation results were verified. The results show that: (i) The maximum error between the model and the experimental data is less than 3.2 %, which verifies the heat transfer model. (ii) As ventilation time increases, the radius of the cooling ring inside the surrounding rock increases in a negative exponential function trend. The annual average unstable heat transfer coefficient falls quickly, and the decrease speed slows down gradually. (iii) With the increase of depth, the amplitude of temperature fluctuation in surrounding rock decreases rapidly in a negative exponential function trend, and the delay phase increases linearly. (iv) The formula of dimensionless wall heat flux wave of surrounding rock was obtained by fitting.